2007
DOI: 10.1073/pnas.0606091104
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of dipeptidyl peptidase I in neutrophil recruitment during the development of experimental abdominal aortic aneurysms

Abstract: Dipeptidyl peptidase I (DPPI) is a lysosomal cysteine protease critical for the activation of granule-associated serine proteases, including neutrophil elastase, cathepsin G, and proteinase 3. DPPI and granule-associated serine proteases have been shown to play a key role in regulating neutrophil recruitment at sites of inflammation. It has recently been suggested that neutrophils and neutrophil-associated proteases may also be important in the development and progression of abdominal aortic aneurysms (AAAs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
122
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 30 publications
5
122
0
1
Order By: Relevance
“…This aortic diameter (AD) remained relatively stable up to day 7, after which there was rapid and significant increase in AD in WT mice (12,18). AAA is typically defined on day 14 as an increase in AD of 100% or greater than the diameter measured before elastase perfusion (12,18). We have previously shown that fB −/− mice are largely resistant to the development of AAA (increase in AD of 105 ± 4%) (12).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This aortic diameter (AD) remained relatively stable up to day 7, after which there was rapid and significant increase in AD in WT mice (12,18). AAA is typically defined on day 14 as an increase in AD of 100% or greater than the diameter measured before elastase perfusion (12,18). We have previously shown that fB −/− mice are largely resistant to the development of AAA (increase in AD of 105 ± 4%) (12).…”
Section: Resultsmentioning
confidence: 99%
“…Properdin is in the plasma and also stored in neutrophil granules, where it is rapidly released during cell stimulation (15,19). To determine whether locally secreted properdin (derived from infiltrating neutrophils) can drive the AAA phenotype, we reconstituted fP −/o mice with purified bone marrow-derived neutrophils using a regimen that we had previously used to successfully restore AAA phenotype in the dipeptidyl peptidase I-deficient mice (18). WT neutrophils (1e7) were injected i.v.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 There is increasing evidence that cathepsin C plays a key role in a variety of diseases, including sepsis, 4 arthritis, 5 and other inflammatory disorders. [6][7][8][9][10][11][12] From knockout mice studies, it appears that cathepsin C is coexpressed and acts as a physiological activator of the neutrophil-derived serine proteases: neutrophil elastase, cathepsin G and proteinase 3,5 the mast cell chymase and trypase, 13 and the lymphocytes derived granzymes A and B.…”
mentioning
confidence: 99%